2011
DOI: 10.2478/s13386-011-0058-x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and origin of organic matter in the Baltic Sea sediments dated with 210Pb and 137Cs

Abstract: Organic carbon deposited in marine sediments is an important part of the global carbon cycle. The knowledge concerning the role of shelf seas (including the Baltic Sea) in the carbon cycle has increased substantially, however organic carbon accumulation rates in the Baltic sediments still require clarification. This paper describes methods used for assessing organic carbon and nitrogen accumulation rates in six sediment cores collected in the sediment accumulation areas in the Baltic Sea. Mass sediment accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Li et al () reported a similar C/N range (1.3–9.9, mean 6.4) in a eutrophic lake, Lake Chaohu (Table ), which has also exhibited a serious algal bloom problem in recent decades. The C/N ratios in the southern and eastern zones exhibited wider ranges than those in the western and northern zones (Figure a,b), as the sources of OM were more complex in the southern and eastern zones and influenced by both internal and terrigenous inputs (Das et al, ; Szczepańska, Zaborska, Maciejewska, Kuliński, & Pempkowiak, ). Overall, relatively high C/N ratios appeared in the eastern and southern zones, particularly in the 2nd investigation (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Li et al () reported a similar C/N range (1.3–9.9, mean 6.4) in a eutrophic lake, Lake Chaohu (Table ), which has also exhibited a serious algal bloom problem in recent decades. The C/N ratios in the southern and eastern zones exhibited wider ranges than those in the western and northern zones (Figure a,b), as the sources of OM were more complex in the southern and eastern zones and influenced by both internal and terrigenous inputs (Das et al, ; Szczepańska, Zaborska, Maciejewska, Kuliński, & Pempkowiak, ). Overall, relatively high C/N ratios appeared in the eastern and southern zones, particularly in the 2nd investigation (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Profiles of organic carbon concentrations in bottom sediments of the Baltic Sea indicate that organic matter concentrations decrease with sediment depth (Emeis et al 2000 ; Szczepańska et al 2012 ). This is attributed to the recent increased organic matter deposition caused by eutrophication (Emeis et al 2000 ; Voss et al 2000 ) and to ongoing mineralization of labile organic matter in deeper sediment layers (Kuliński and Pempkowiak 2011 ; Szczepańska et al 2012 ). The mineralization occurs in two stages: the first lasting some 10 years, and the second lasting 50–60 years (Kuliński and Pempkowiak 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Organic carbon burial in bottom sediments of the Baltic Sea was calculated as the difference between organic carbon accumulated in deep depositional areas of the Baltic Sea and organic matter losses due to long-term mineralization and diffusion into the water column. Carbon accumulation rates were determined from sediment accumulation rates based on the 210 Pb method and validated against the 137 Cs distribution (Pempkowiak 1991 ; Szczepańska et al 2012 ) and from organic carbon concentrations in the sediments. Carbon losses caused by long-term mineralization were calculated from concentrations of inorganic carbon dissolved in pore water and from diffusion into the water column, where they contribute to accumulated total CO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This artificial radionuclide was introduced into the environment in a huge amount during nuclear weapon tests (1945–1965) and was emitted to the atmosphere during the Chernobyl accident (1986) (UNSCEAR 2000 ). Fallout from 137 Cs and 210 Pb have been widely used to establish the chronology of sediment cores collected from various aquatic systems (McCall et al 1984 ; Ritchie and McHenry 1990 ; Walling and He 1992 ; Aycik et al 2004 ; Klaminder et al 2012 ; Szczepanska et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%